Lymphedema secondary to idiopathic occlusion of the subclavian and innominate veins after renal transplantation: A case report. Issue 48 (December 2017) - Kim, Yong Min; Moon, Chul; Goo, Dong Erk; Park, Soo Bin; Park, Ji Woong
Abstract: Rationale: Among the causes of swelling in the extremities of renal transplantation patients, secondary lymphedema caused by complete idiopathic obstruction of large veins is rare and may be difficult to diagnose and treat. Patient concerns: A 64-year-old man presented with severe edema and pain that occurred suddenly in the right arm. Diagnoses: The patient was diagnosed as stage-2 secondary lymphedema caused by idiopathic occlusion of the subclavian and innominate veins. Interventions: Lymphoscintigraphy and ascending venography of the right arm confirmed the diagnosis. Intensive complete decongestive therapy for lymphedema was performed. Outcomes: Following 2 weeks of active rehabilitation, the pain level and edema status were significantly improved. Lessons: When idiopathic swelling of the extremities occurs in renal transplant patients, secondary lymphedema caused by venous occlusion may be the cause. When direct intervention for the venous occlusion proves to be difficult, a conservative approach may be helpful.